Ramuan dan Pengobatan Tradisional Pulau Penyengat untuk Sakit yang Berkaitan dengan Mata - Wahyuni, Indah; Widyatwati, Ken (Jurnal Bahasa dan Sastra, 2024)
The manuscript of Pengobatan Tradisional pada Masyarakat Pulau Penyengat (PTpMPP) contains various types of pain along with herbal ingredients, one of which is pain related to the eyes. The purpose of this study is to explain the study of ethnomedicine contained in the text of PTpMPP. The methods used are data collection, data processing, data analysis, and presentation of the results of data analysts. The data collection phase was carried out by field studies and literature studies. The data processing stage is carried out from the description of the manuscript, transliteration, and text editing. In studying its content, researchers used the theory of ethnomedicine. Studies that combine literature and ethnomedicine can provide a better understanding of how language, culture and narrative shape medical perceptions and practices in a given society. In addition, it can help improve interdisciplinary understanding of the human complexity of understanding and addressing health issues because literary works, particularly ancient texts, can reflect and shape the traditional medical knowledge and practices of different cultures. This makes it possible to understand health and medicine in a broader and more complex cultural context. Therefore, ethnomedicine is used to reveal the kinds and functions of medicinal plants used and the treatment methods contained in ancient manuscripts. The source of the data used is PTpMPP manuscript with Jawi script and Malay script, stored in Yayasan Inderasakti, Pulau Penyengat. The results of this study explain the eight causes of pain related to the eyes, namely injured eyes, eye pain (ordinary), blurred eyes, growing eyes, meat eye pain, restung eye pain, swollen eyes, and eyes for prohibition. The medical practice of treating the eight diseases belongs to the naturalistic medical system and each disease has its own herbal ingredients.